1980
DOI: 10.1128/aac.18.6.948
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Campylobacter jejuni and Campylobacter fetus subsp. fetus to eight cephalosporins with special reference to species differentiation

Abstract: Agar dilution antimicrobial susceptibility testing showed that Campylobacter jejuni was significantly more resistant than Campylobacter fetus subsp. fetus (intestinalis) to cephalosporin C, cephaloridine, cephalothin, cefazolin, and cefamandole. No species differences in susceptibility were noted with cephalexin, cefotaxime, and cefoxitin. Rapid species differentiation on the basis of an antibiogram could be achieved with the disk diffusion method. C jejuni failed to produce a zone of inhibition around a 30-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 11 publications
1
26
1
Order By: Relevance
“…Our results show that the hog strains are more resistant to tetracycline than the human strains. Studies of other human isolates showed a MIC9o range of 0.5 to 64 ,ug of tetracycline per ml (7,11). These differences might also be related to the ultimate source of strains tested.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show that the hog strains are more resistant to tetracycline than the human strains. Studies of other human isolates showed a MIC9o range of 0.5 to 64 ,ug of tetracycline per ml (7,11). These differences might also be related to the ultimate source of strains tested.…”
Section: Resultsmentioning
confidence: 99%
“…fetus by their susceptibility to <40 p.g of nalidixic acid per ml (12,24,25). CLO type 1 and 2 strains were susceptible to cefazolin but strains of C. jejuni that are susceptible to this antimicrobial agent have not been reported (11,15).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows that the derived amino acid sequence of the aacA4 allele from Campylobacter demonstrated 100% homology to the AAC(6Ј)-Ib 7 enzyme, which has been shown to confer characteristics resulting in higher kanamycin and tobramycin MICs but only slightly increased resistance to gentamicin (5). To evaluate the phenotype conferred by the AAC(6Ј)-Ib 7 enzyme in C. jejuni, four of the isolates containing aacA4 were assayed for tobramycin and gentamicin resistance, using agar dilution on Mueller-Hinton agar containing 5% washed sheep red blood cells (19). Table 1 shows that for the int ϩ aacA4 ϩ strains tested, tobramycin MICs were 25 to 50 g/ml and gentamicin MICs were 10 to 50 g/ml.…”
mentioning
confidence: 99%